2023
DOI: 10.1021/acs.chemmater.3c00202
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Control of Magnetism on the Breathing Kagome Network of LixScMo3O8

Abstract: Controlling properties within a given functional inorganic material structure type is often accomplished through tuning the electronic occupation, which is in turn dictated by the elemental composition determined at the time of material preparation. We employ electrochemical control of the lithium content, with associated electronic occupancy control, to vary the magnetic properties of a material where a kagome-derived network of Mo3 triangles carry the spin. In this case, Li is electrochemically inserted into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…The formation of metal–metal dimers to accommodate the charge donated by Li falls into a class of molecular-orbital like redox mechanisms that is increasingly being explored as an alternative to cation-centric redox mechanisms of conventional battery intercalation compounds. , Other compounds exhibiting molecular-orbital redox mechanisms include Na 2 Mn 3 O 7 and Li x ScMo 3 O 8 . , In Na 2 Mn 3 O 7 , redox has been predicted to occur on antibonding states distributed over an extended ring of π-bonded Mn and oxygen orbitals surrounding a cation vacancy . In Li x ScMo 3 O 8 , charge donated by Li is accommodated on molecular orbital-like states derived from Mo metal trimer clusters formed by the hybridization of t 2g orbitals. , …”
Section: Discussionmentioning
confidence: 99%
“…The formation of metal–metal dimers to accommodate the charge donated by Li falls into a class of molecular-orbital like redox mechanisms that is increasingly being explored as an alternative to cation-centric redox mechanisms of conventional battery intercalation compounds. , Other compounds exhibiting molecular-orbital redox mechanisms include Na 2 Mn 3 O 7 and Li x ScMo 3 O 8 . , In Na 2 Mn 3 O 7 , redox has been predicted to occur on antibonding states distributed over an extended ring of π-bonded Mn and oxygen orbitals surrounding a cation vacancy . In Li x ScMo 3 O 8 , charge donated by Li is accommodated on molecular orbital-like states derived from Mo metal trimer clusters formed by the hybridization of t 2g orbitals. , …”
Section: Discussionmentioning
confidence: 99%
“…An alternative is to identify alloying elements that do not favor metal–metal dimer formation and also segregate to the edge-sharing octahedra at the shear boundaries. Wadsley–Roth phases containing Nb, V, and Mo, which are known to readily form metal–metal bonds, should then be alloyed with elements that have a lower oxidation state. Alloying elements having a low maximum oxidation state will tend to segregate to the edge-sharing octahedra along the crystallographic shear planes and thereby relegate the metal-dimer formers such as Nb, V, and Mo to corner-sharing octahedra where they are unable to form metal–metal bonds.…”
Section: Discussionmentioning
confidence: 99%
“…From our examination of redox mechanisms in two Nb 2 O 5 polymorphs, we have found that metal–metal bond formation, responsible for significant strain in TiNb 2 O 7 , also occurs in Nb 2 O 5 , suggesting a universality of the metal–metal bond redox mechanism in Wadsley–Roth phases. The dimer redox mechanism belongs to a class of redox processes that occur on extended molecular orbitals. , …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations